Using quality improvement tools to enhance workplace learning in an anaesthesia unit. (1st November 2020) - Foong, Theng Wai; Tiong, Hui-Fen; Ong, Say Yang; Chen, Fun Gee
Abstract: Background: In healthcare, quality improvement (QI) tools are predominantly used to address human, system and process factors to improve clinical care. We believe that QI tools can also be used to address similar factors in medical education, to facilitate improvement in learning outcomes and competencies for new junior doctors in a postgraduate medical education program in our anaesthesia and critical care unit. Methods: A stepwise competency checklist was devised to guide the learning and monitor the percentage who had completed the required learning activities and tests at the end of each month. This was tabulated as monthly competency scores, and served as a measure of effectiveness of the education program. QI tools, namely the Fishbone diagram and Pareto chart, were used to identify modifiable root causes and prioritise interventions. Results: Monthly competency scores ranged 30–50% at baseline, and improved to 60–75% after 6 months, with the implementation of a series of QI interventions. Conclusion: QI tools were utilised to guide education interventions, with consequent improvement in the monthly competency scores of our junior doctors. Focused improvement cycles that are aligned to learning outcomes are key to the success of using QI tools in medical education.